1998
DOI: 10.1002/(sici)1099-114x(199802)22:2<131::aid-er345>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

An analytical solution of the heat transfer process during contact melting of phase change material inside a horizontal elliptical tube

Abstract: SUMMARYClose-contact melting processes of phase change material (PCM) inside a horizontal elliptical tube are studied. The theoretical formulas of the melting rate, thickness of liquid layer, elapsed time of solid PCM and Nusselt number during the heat melting process are obtained by analyzing. The results include those of contact melting inside a horizontal cylinder. Finally, the influences of elliptical compression coefficient and temperature difference in melting are discussed, and useful conclusions are dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…In the last decades, a higher number of analytical [30][31][32][33][34][35][36][37] as well as numerical methods [38][39][40][41][42][43] were developed to describe the melting and freezing process of a material under the influence of gravity. The main problem concerning the numerical simulation of the melting and/or solidification process is the change with time of the position of the phase interface.…”
mentioning
confidence: 99%
“…In the last decades, a higher number of analytical [30][31][32][33][34][35][36][37] as well as numerical methods [38][39][40][41][42][43] were developed to describe the melting and freezing process of a material under the influence of gravity. The main problem concerning the numerical simulation of the melting and/or solidification process is the change with time of the position of the phase interface.…”
mentioning
confidence: 99%
“…However, when the solid density is more than that of the liquid PCM, the solid core moves downward during the melting process driven by the gravity force (sink effect). This effect is investigated in previous studies [22][23][24][25][26][27]. But, when there is no significant difference in the density, as in the present case, the solid core does not sink and the liquid is constrained.…”
Section: Liquid Fraction Status and Melt Streamlinesmentioning
confidence: 45%
“…In addition, the tubes of elliptic section may be an alternative for circular tubes when there is space restriction. Chen et al [18] investigated analytically melting of n-octadecane in a horizontal elliptic cylinder. They concluded that the melting rate in the elliptic enclosure is higher than that in the circular cylinder of the same cross sectional area.…”
Section: Introductionmentioning
confidence: 99%